Concern on Skin Lightening Product Safety: Level of Awareness and Associated Factors Among Female Users in Bahir Dar City, Ethiopia - Yayehrad AT; Lule A; Tebabal AT; Esmael M; Risqey N; Temesgen S; Negash S; Hamid S; Tasew S; Mekonen S; Siraj EA (Dove Medical Press, 2023)
Ashagrachew Tewabe Yayehrad,1 Abel Lule,2 Adugna Tasew Tebabal,2 Muhammed Esmael,3 Nuralhuda Risqey,3 Samrawit Temesgen,3 Selam Negash,3 Selama Hamid,3 Silenat Tasew,3 Sosina Mekonen,3 Ebrahim Abdela Siraj1 1Department of Pharmacy, School of Health Sciences, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 2Dean Office, GAMBY Medical and Business College, Bahir Dar, Ethiopia; 3Department of Pharmacy, School of Medicine, GAMBY Medical and Business College, Bahir Dar, EthiopiaCorrespondence: Ashagrachew Tewabe Yayehrad, Department of Pharmacy, School of Health Sciences, College of Medicine and Health Sciences, Bahir Dar University, PO BOX: 79, Bahir Dar, Ethiopia, Tel +251 912 960 525, Email ashutewabe@gmail.comBackground: Most skin lightening products are composed of some toxic chemicals such as mercury and hydroquinone which are classified under critical ingredients which need evaluation. Consumption without sufficient awareness may lead to toxicities endangering skin health.Objective: The aim of this study was to assess the level of awareness towards the side effects of skin lightening products and associated factors among females in Bahir Dar city, Ethiopia.Methods: An institutional-based cross-sectional study design was conducted in Bahir Dar city from June 28 to August 28, 2022 among females that had been using skin whitening. Samples of 362 females were selected by using multistage sampling technique from selected drug retail outlets. The data was coded, cleaned, and analyzed by using SPSS version 26. The variables were analyzed through multiple regression in order to identify the associated factors towards the level of awareness on the side effects of skin lightening products.Results: Only 42.7% of the respondents had a favorable level of awareness. The highly influencing factors for using skin lightening products were peer pressure (39.9%) and social media (37.4%). Nearly half of the users experienced side effects. Only 8.9% of the respondents know the active ingredients of the products. Level of education was found to have significant association with level of awareness (AOR = 7.66, 95% CI: (1.23, 47.59); P = 0.029).Conclusion: Only less than half of women have favorable awareness towards skin lightening products they use. The significant association between educational level and level of awareness should be considered as an alternative intervention in addition to regulatory restrictions.Keywords: skin lightening product, awareness, safety, side effects, Ethiopia